THE EFFECT OF INFORMATION TECHNOLOGY UTILIZATION ON THE QUALITY OF ONLINE LEARNING - Peliza, Rahman (International Journal of Multidisciplinary Reseach, 2025)
The rapid development of information technology has encouraged the implementation of online learning in higher education. Optimal utilization of information technology has become a crucial factor in improving the quality of online learning for students. This study aims to analyze the effect of information technology utilization on the quality of students’ online learning. The study employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to students participating in online learning. The variables examined include the level of information technology utilization and the quality of students’ online learning, which encompasses aspects of learning interaction, ease of access, effectiveness of content delivery, and learning satisfaction. The data were analyzed using statistical analysis techniques to determine the influence between the independent and dependent variables. The results indicate that the utilization of information technology has a positive and significant effect on the quality of students’ online learning. These findings suggest that effective utilization of information technology can enhance student engagement, the effectiveness of the learning process, and the overall quality of online learning in higher education. This study is expected to serve as a reference for higher education institutions in designing more effective online learning strategies that are oriented toward students’ needs.